The Requirements of Teaching Competencies for Faculty Members of Colleges of Physical Education and Sports Sciences in Light of Technological Transformations in Artificial Intelligence at the Universities of Baghdad (Journal of the College of Basic Education, 2025)
The researcher recommended that the use of artificial intelligence tools should become an integral part of every lesson plan or educational presentation, rather than an optional supplement, while ensuring a balance between physical and technical aspects. Educational activities should be developed in a way that allows for the collection and analysis of student behavioral data, enabling the creation of personalized and precise pedagogical interventions based on each student’s needs. Additionally, the use of AI technologies such as simulation or visual analysis should take into account individual differences among students in terms of technical and motor abilities. It is also advisable to utilize intelligent platforms that enable two-way interaction and provide accurate indicators of engagement, which can support the adaptation of communication styles based on actual analysis.